Optimal allometric biomass equations for Hornbeam (Carpinus betulus L.) boles within the Hyrcanian forests - Ali Asghar Vahedi (تحقیقات جنگل و صنوبر ایران, 2014)
According to the amount of carbon emitted to the atmosphere, obtaining accurate estimations of biomass is an effective step to deal with the global warming and climate change on various spatial scales. Therefore, this study pursued the aim of investigating allometric models to increase the accuracy of the dry biomass calculation for hornbeam (Carpinus betulus L.), which is one of the most abundant tree species across the Hyrcanian forests of Iran. The diameter at breast height, bole height and age were used as explanatory variables in non-linear models (power and exponential functions) and as combined variables in linear, log-transformed models. The results showed that the power and exponential functions of diameter returned the best fit and highest accuracy (R2adj= 0.72-0.75; SEE = 0.53-0.51). For the entire combined variables, the squares diameter and height (dbh2 × h) was the best combination, showing the highest correlation with the observations. Subsequently, the log-transformed model containing the mentioned combined variables returned the highest estimation accuracy (R2adj= 0.77; SEE = 0.48) and best fit-goodness. Regarding the acquired variance inflation factor (VIF >10), the multiple linear models were not significant. Furthermore, the least correction factor was calculated (CF = 1.11) to correct for the model bias. Therefore, the optimal model of Y = Exp [-3.47 + 1.007 ln(dbh2 ×h) was introduced to estimate bole biomass of hornbeam.